Chrysophanol from aloe sap : isolation, characterization and biological activity study / Pat M. Lee, Hannis Fadzillah Mohsin and Kong Hung Lee - Lee, Pat M.; Mohsin, Hannis Fadzillah; Kong, Hung Lee (Faculty of Applied Sciences, 2005)
A compound was isolated by organic solvent extraction and solvent partition method from Aloe sap and purified by chromatographic methods. It was characterized by various spectroscopic methods and was found to be consistent with the structure of chrysophanol (l,8-dihydroxy-3-methylanthraquinon). It was assayed for anti-oxidant activity using ferric thiocyanate-linoleic acid system, DPPH radical scavenging method and reducing power. It was found that it was not an antioxidant.